The house dust mite allergen Der p 5 binds lipid ligands and stimulates airway epithelial cells through a TLR2‐dependent pathway. Issue 3 (12th October 2018) - Pulsawat, Pinya; Soongrung, Tewarit; Satitsuksanoa, Pattraporn; Le Mignon, Maxime; Khemili, Souad; Gilis, Dimitri; Nony, Emmanuel; Kennedy, Malcolm W.; Jacquet, Alain
Abstract: Background: Protein crystallographic studies suggest that the house dust mite (HDM) allergen Der p 5 potentially interacts with hydrophobic ligands. Der p 5, in association with its ligand(s), might therefore trigger innate immune signalling pathways in the airway epithelium and influence the initiation of the HDM‐allergic response. Objective: We investigated the lipid binding propensities of recombinant (r)Der p 5 and characterized the signalling pathways triggered by the allergen in airway epithelial cells. Methods: rDer p 5 was produced in Pichia pastoris and characterized by mass spectrometry, multi‐angle light scattering and circular dichroism. Its interactions with hydrophobic ligands were investigated in fluorescence‐based lipid binding assays and in‐silico docking simulations. Innate immune signalling pathways triggered by rDer p 5 were investigated in airway epithelial cell activation assays in vitro. Results: Biophysical analysis showed that rDer p 5 was monomeric and adopted a similar α‐helix‐rich fold at both physiological and acidic pH. Spectrofluorimetry experiments showed that rDer p 5 is able to selectively bind lipid ligands, but only under mild acidic pH conditions. Computer‐based docking simulations identified potential binding sites for these ligands. This allergen, with putatively associated lipid(s), triggered the production of IL‐8 in respiratory epithelial cells through a TLR2‐, NF‐kB‐ and MAPK‐dependent signalling pathway. Conclusions and Clinical Relevance: Despite the fact that Der p 5 represents a HDM allergen of intermediate prevalence, our findings regarding its lipid binding and activation of TLR2 indicate that it could participate in the initiation of the HDM‐allergic state.